A Case of Primary Renal Carcinoid Tumor. (22nd January 2015) - Tanaka, Toshikazu; Yamamoto, Hayato; Imai, Atsushi; Shingo, Hatakeyama; Yoneyama, Takahiro; Koie, Takuya; Hashimoto, Yasuhiro; Ohyama, Chikara
Abstract : Primary renal carcinoid tumors are extremely rare kidney lesions, with fewer than 100 reported cases previously. We describe a 75-year-old man with an incidentally detected cystic renal mass. Computed tomography showed a 3 cm tumor with a cystic component enhanced with contrast. No evidence of metastasis was detected. We treated the patient with radical nephrectomy. Pathological examinations revealed a cellular arrangement specific to carcinoid tumor and positive for chromogranin A, neural cell adhesion molecule, and somatostatin receptor type 2. The tumor cells had a mitotic count of 4 mitoses/10 high-power fields, and the level of the proliferation marker Ki-67 was 5%. The pathological diagnosis was renal neuroendocrine tumor grade 2. No local recurrence and no systemic metastasis were detected during the 18-month follow-up period. To our knowledge, this is the 6th case of renal neuroendocrine grade 2 tumor reported thus far.